Cytochrome P-450 Polymorphisms and Response to Clopidogrel - Mega, Jessica L; Close, Sandra L; Wiviott, Stephen D; Shen, Lei; Hockett, Richard D; Brandt, John T; Walker, Joseph R; Antman, Elliott M; Macias, William; Braunwald, Eugene; Sabatine, Marc S (The New England journal of medicine, 2009)
The antiplatelet drug clopidogrel requires activation by cytochrome P-450 (CYP) enzymes. This study shows that CYP polymorphisms that reduce clopidogrel activation result in reduced antiplatelet effect and less clinical benefit in patients with acute coronary syndromes. The antiplatelet drug clopidogrel requires activation by cytochrome P-450 (CYP) enzymes. This study shows that CYP polymorphisms that reduce clopidogrel activation result in reduced antiplatelet effect and less clinical benefit in patients with acute coronary syndromes. Across the spectrum of acute coronary syndromes and in patients undergoing percutaneous coronary interventions (PCI) with stenting, dual antiplatelet therapy with aspirin and clopidogrel, a thienopyridine inhibitor of the platelet P2Y 12 adenosine diphosphate (ADP) receptor, is the standard of care. 1 – 3 However, the pharmacodynamic response to clopidogrel has substantial interpatient variability, 4 – 6 and patients with coronary disease with lesser degrees of platelet inhibition in response to clopidogrel appear to be at increased risk for cardiovascular events. 7 – 10 Clopidogrel is a prodrug that requires biotransformation to an active metabolite by cytochrome P-450 (CYP) enzymes (Figure 1 in the Supplementary Appendix, available . . .